Sustainability of Transport Projects : Toolkit - World Bank (World Bank, Washington, DC, 2017)
This report is the output of the finalize toolkit phase (phase three) for the project sustainability toolkit for transport projects. The overall objective, as defined in the terms of reference, is 'to make development projects more sustainable by reducing the risk of failure of projects attaining their long-term development goals and enhance the prospects for their sustained impact on development ensuring that there is local commitment to longer-term buy-in'. The main deliverable of the project is a project sustainability toolkit, of which this report outlines the final version. This toolkit helps to gauge the potential for the project to be sustainable into the long-term and provide advice to help overcome common barriers to the successful development and implementation of projects. The guidance covers the expected opportunities and constraints related to sustainability. The toolkit is intended to reduce the risk of project failure in terms of sustainable development and enable recipient country clients to incorporate core sustainability principles into transport projects at every stage of project planning, design and delivery. This will improve the prospects for longer-term sustainability and will enhance the long-term impacts of development projects. Task Team Leaders (TTL's) will benefit from additional evidence that supports investments intended to consolidate long-term development, and borrowers will benefit from projects with improved and demonstrable longer-term beneficial impact. The toolkit provides general advice for transport sector investments and is not modally specific. Information on the sub-components of the key sustainability principles has not been included since it was considered that this did not add value or further understanding of the issues.